Enrichment of Ly6Chi monocytes by multiple GM-CSF injections with HBV vaccine contributes to viral clearance in a HBV mouse model - Weidong Zhao; Xian Zhou; Gan Zhao; Qing Lin; Xianzheng Wang; Xueping Yu; Bin Wang (Taylor & Francis Group, 2017)
Adjuvants are considered a necessary component for HBV therapeutic vaccines but few are licensed in clinical practice due to concerns about safety or efficiency. In our recent study, we established that a combination protocol of 3-day pretreatments with GM-CSF before a vaccination (3 × GM-CSF+VACCINE) into the same injection site could break immune tolerance and cause over 90% reduction of HBsAg level in the HBsAg transgenic mouse model. Herein, we further investigated the therapeutic potential of the combination in AAV8-1.3HBV-infected mice. After 4 vaccinations, both serum HBeAg and HBsAg were cleared and there was a 95% reduction of HBV-positive hepatocytes, in addition to the presence of large number of infiltrating CD8+ T cells in the livers. Mechanistically, the HBV-specific T-cell responses were elicited via a 3 × GM-CSF+VACCINE-induced conversion of CCR2-dependent CD11b+ Ly6Chi monocytes into CD11b+CD11c+ DCs. Experimental depletion of Ly6Chi monocytes resulted in a defective HBV-specific immune response thereby abrogating HBV eradication. This vaccination strategy could lead to development of an effective therapeutic protocol against chronic HBV in infected patients.